Tanggung Jawab Warga Negara Asing Sebagai Penyewa Kendaraan Bermotor Atas Kerusakan Kendaraan Bermotor di Kabupaten Badung - Ni Kadek Iwantari Putri; I Nyoman Putu Budiartha; I Wayan Werasmana Sancaya (Jurnal Analogi Hukum, 2024)
The advancement of the tourism sector in Bali has caused many foreign tourists to want to visit Bali. The surge in the need for vehicles for traveling has led to motorcycle rentals in the Badung Regency area. This study attempts to find out the responsibility of foreign nationals in the event of damage to motorized vehicles and to find out how efforts are made to deal with damage to motorized vehicles in Badung Regency.  The results of the study prove that the responsibility of the renter in the event of damage to the motor vehicle in a written or oral agreement. In the lease agreement that has been mutually agreed upon if there is damage to the tenant is obliged to compensate for the losses experienced. Both parties must pay more attention to the clauses of the agreement to be agreed upon, especially in the event of damage to the motorized vehicle, so that a written agreement is made and there is no more oral agreement. Not only that, the renter is expected to read and master the contents of the agreement, as a result there is no negligence that can lead to losses for the renting party or motorcycle rental.